Statistical matching for conservation science. Issue 3 (24th December 2019) - Schleicher, Judith; Eklund, Johanna; D. Barnes, Megan; Geldmann, Jonas; Oldekop, Johan A.; Jones, Julia P. G.
Abstract: The awareness of the need for robust impact evaluations in conservation is growing and statistical matching techniques are increasingly being used to assess the impacts of conservation interventions. Used appropriately matching approaches are powerful tools, but they also pose potential pitfalls. We outlined important considerations and best practice when using matching in conservation science. We identified 3 steps in a matching analysis. First, develop a clear theory of change to inform selection of treatment and controls and that accounts for real‐world complexities and potential spillover effects. Second, select the appropriate covariates and matching approach. Third, assess the quality of the matching by carrying out a series of checks. The second and third steps can be repeated and should be finalized before outcomes are explored. Future conservation impact evaluations could be improved by increased planning of evaluations alongside the intervention, better integration of qualitative methods, considering spillover effects at larger spatial scales, and more publication of preanalysis plans. Implementing these improvements will require more serious engagement of conservation scientists, practitioners, and funders to mainstream robust impact evaluations into conservation. We hope this article will improve the quality of evaluations and help direct future research to continue to improve the approaches on offer. Abstract : Article Impact statement : The article identifies 3 steps in using matching in conservation impact evaluation, highlighting best practice and areas for improvement. Abstract : Emparejamiento Estadístico para la Ciencia de la Conservación Resumen: Hay más conciencia sobre la necesidad de evaluaciones de impacto más rigurosas y las técnicas de emparejamiento estadístico se están usan con más frecuencia para evaluar los impactos de intervenciones de conservación. Las técnicas de emparejamiento pueden ser herramientas poderosas si son utilizadas correctamente, pero también pueden llevar a conclusiones erróneas. En este artículo describimos consideraciones importantes para realizar estudios de conservación que utilizan técnicas de emparejamiento estadístico. Identificamos tres pasos dentro de un análisis de emparejamiento. Primero, es importante desarrollar una teoría del cambio que considere las complejidades del mundo real y las posibles consecuencias indirectas para poder seleccionar unidades de tratamiento y controles. Segundo, es clave seleccionar las covarianzas y la estrategia de emparejamiento apropiadas. Tercero, evaluar la calidad del emparejamiento a través de una serie de revisiones. El segundo y el tercer paso pueden ser repetidos y deben concluirse antes de que se exploren los resultados. Evaluaciones de impacto de intervenciones de conservación podrían mejorarse con una mejor planeación de las evaluaciones junto con la intervención, una mejor integración de los métodos cualitativos, mejor consideración de consecuencias indirectas a grandes escalas espaciales y un incremento en la publicación de planes pre‐analíticos. La implementación de estas mejoras requerirá de un compromiso más serio por parte de científicos de la conservación, y de practicantes y financiadores. Esperamos que este artículo mejore la calidad de evaluaciones y ayude a guiar futuras investigaciones e intervenciones de conservación. 摘要: 目前, 已经有越来越多的人认识到需要对保护的效果进行稳健的评估, 在评估保护措施的影响时也越来越多地应用了统计匹配方法。匹配方法若使用得当可成为有力工具, 但也可能带来潜在陷阱。本研究概述了在保护科学中使用匹配方法时的重要注意事项和最佳实践。我们确定了匹配分析的三个步骤。首先是提出清晰的变化理论来指导实验组和控制组的选择, 其中要考虑到现实世界的复杂性和潜在的溢出效应。接下来, 应选择合适的协变量和匹配方法。最后, 需通过一系列的检查来评估匹配的质量。第二步和第三步可以重复进行, 但要在输出匹配结果前完全确定。在实施保护措施的同时加强评估规划、更好地整合总结定性方法、考虑更大空间尺度的溢出效应, 以及更多地公开发表预分析计划, 将有助于改善未来的保护效果评估体系。实施以上改进措施还需要保护科学家、实践者和资助者的认真参与, 推动保护效果的稳健评估纳入保护工作的主流。我们希望本文有助于提升保护效果评估的质量, 并帮助指导今后的研究以进一步改进现有的方法。【翻译: 胡怡思; 审校: 聂永刚】